Case Report: Lipoprotein Glomerulopathy Complicated by Atypical Hemolytic Uremic Syndrome - Kollbrunner, Lara; Hirt-Minkowski, Patricia; Sanz, Javier; Bresin, Elena; Neuhaus, Thomas J.; Hopfer, Helmut; Jehle, Andreas W. (Frontiers in Medicine, 2021)
Lipoprotein glomerulopathy (LPG) is a rare inherited disease caused by mutations in the APOE gene, encoding apolipoprotein E (apoE). Atypical hemolytic uremic syndrome (aHUS) is a thrombotic microangiopathy (TMA) characterized by overactivation of the alternative complement pathway. Here we report the case of a 21-year-old man with LPG who developed aHUS. A functional complement assay demonstrated an overactivation of the complement system. Complementary genetic analysis revealed a homozygous aHUS risk allele for complement factor-H related 1 (CFHR1), CFHR1*B. To the best of our knowledge, this is the first report of an aHUS in a patient with LPG.